Mapping the premigration distribution of eastern Monarch butterflies using community science data. Issue 16 (14th July 2021) - Momeni‐Dehaghi, Iman; Bennett, Joseph R.; Mitchell, Greg W.; Rytwinski, Trina; Fahrig, Lenore
Abstract: Knowing the distribution of migratory species at different stages of their life cycle is necessary for their effective conservation. For the Monarch butterfly ( Danaus plexippus ), although its overwintering distribution is well known, the available information on premigration distribution is limited to the studies estimating the natal origins of overwintering Monarchs in Mexico (i.e., postmigration data). However, the premigration distribution and the natal origins of overwintering Monarchs can be equivalent only if we assume that migrating Monarchs have the same mortality rate irrespective of their origins. To estimate Monarchs' premigration distribution, we used data reported by community scientists before Monarchs start their fall migration, that is, before migration mortality, and controlled for sampling bias. Our premigration distribution map indicated that Minnesota, Texas, and Ontario are the states/provinces with the highest abundance of Monarch in North America. Although this higher estimated abundance can be related to the large sizes of these states/provinces, this information is still important because it identifies the management jurisdictions with the largest responsibility for the conservation of the premigration population of Monarchs. Our premigration distribution map will be useful in future studies estimating the rates, distribution, and causes of mortality in migrating Monarchs. Abstract : Our paper provides the first quantitative estimate of the premigration distribution of Monarch butterflies across North America. Our results showed that Minnesota, Texas, and Ontario are the states/provinces with the highest abundance of Monarchs before they start their fall migration. This information is important because it identifies the management jurisdictions with the largest responsibility for the conservation of the premigration population of Monarchs. Our premigration distribution map will be useful in future studies estimating the rates, distribution, and causes of mortality in migrating Monarchs.